2013
DOI: 10.1186/1471-2334-13-146
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile infection in Italian urban hospitals: data from 2006 through 2011

Abstract: BackgroundIn developed countries, Clostridium difficile infection (CDI) represents an emerging threat in terms of morbidity and mortality rates. In our country limited CDI epidemiological data can be found.We have conducted a 6-year retrospective study to evaluate the incidence of CDI in Italian urban hospitals.MethodsStool samples tested for C. difficile toxins from January 2006 to December 2011 in 5 large hospitals in Rome, Italy, were considered in the analysis. Repeated samples taken ≤ 2 months after a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
10
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
6
10
0
3
Order By: Relevance
“…A very recent study, conducted in five hospitals in Rome over a 6-year period (2006 to 2011), reported an increase in the CDI incidence from 0.84 to 2.3 per 10,000 patient-days (29). In our study, we observed higher CDI rates, with an average value of 3.05 episodes per 10,000 patientdays, perfectly overlapping with incidence data of other similar hospitals of the Lombardy region.…”
Section: Discussionsupporting
confidence: 77%
“…A very recent study, conducted in five hospitals in Rome over a 6-year period (2006 to 2011), reported an increase in the CDI incidence from 0.84 to 2.3 per 10,000 patient-days (29). In our study, we observed higher CDI rates, with an average value of 3.05 episodes per 10,000 patientdays, perfectly overlapping with incidence data of other similar hospitals of the Lombardy region.…”
Section: Discussionsupporting
confidence: 77%
“…[11][12][13] However, country-specific studies in Spain and Italy indicate that the prevalence of CDI is increasing: between 1999 and 2007, the prevalence rate increased from 3.9-12.2 per 100 000 population in Spain, 14 with more recent data indicating that rates remain high (13.4-22.5 per 100 000) and suggesting that CDI is underdiagnosed due to the diagnostic methods used; 15,16 in Italy, the incidence of CDI in five large hospitals in Rome increased significantly (p < 0.001) over the 6-year period between 2006 and 2011 (from 0.3-2.3 episodes per 1000 patient-days). 17 The resource burden of CDI is considerable. A retrospective cohort study of infected (n = 38) and matched non-infected (n = 76) patients conducted during an outbreak of nosocomial CDI in Spain in 2006, demonstrated that patients who developed CDI were exposed to more antibiotics, had higher mortality, and were hospitalized for longer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cases of healthcare-associated carbapenem resistant K. pneumoniae BSIs have been reported in Northern Italy [3]. The phenomenon is also well known in Rome [4] and parallels to an epidemiological shift of CDI occurring in our region and consisting of increased disease incidence and mortality rates [5, 6], that are probably due to the spread of the epidemic strain ribotype 027 CD [68]. In the present case, because the initial diagnosis was made in a peripheral center, ribotyping test was not performed.…”
Section: Discussionmentioning
confidence: 99%